Percutaneous Pulmonary Valve Implantation in the Native Right Ventricular Outflow Tract Using a 29-mm Edwards SAPIEN 3 Valve. (September 2017) - Suntharos, Patcharapong; Prieto, Lourdes R.
Percutaneous pulmonary valve implantation is now an acceptable treatment option. The Edwards SAPIEN valve, intended for transcatheter aortic valve implantation, has been used in patients whose landing zone diameter is >22 to 24 mm which is not suitable for Melody valve. We report a patient in whom we successfully placed the latest generation, Edwards SAPIEN 3 (ES3) in the pulmonary position. However, because of the short covered portion of this valve, there was a significant paravalvular leak through the stent struts requiring implantation of a second ES3 valve.